Chromosome numbers in hybrids between invasive and native Solidago (Asteraceae) species in Europe - Musiał, Krystyna; Pagitz, Konrad; Gudžinskas, Zigmantas; Łazarski, Grzegorz; Pliszko, Artur (Phytotaxa, 2020)
In Europe, two North American species, Solidago canadensis and S. gigantea hybridize with native S. virgaurea producing the hybrids: S. ×niederederi, a hybrid between S. canadensis and S. virgaurea, and S. ×snarskisii, a hybrid between S. gigantea and S. virgaurea. The morphological description of both hybrids has been well established in contrast to the data on chromosome numbers which were insufficiently recorded or missing. The diploids of S. ×niederederi have been recently reported from a few localities in Austria and Lithuania. In this study, we evidenced a triploid of S. ×snarskisii from one locality in Lithuania, as well as confirmed diploids in the progenies of S. ×niederederi collected in 23 new localities in Austria, Poland, Lithuania, and Latvia, based on chromosome counting.